Pedagogical management in the digital educational environment: Theoretical aspect - S. S. Kulikova; O. V. Yakovleva (Образование и наука, 2022)
Introduction. The digital educational environment is becoming not only a challenge of the new time, but also an important condition, a means of training a specialist of the new formation for the digital society. In the digital environment, a teacher will have to learn how to organise, accompany and support the educational activities of students, build network interaction, exercise control and assessment, and create flexible personalised mastering of content. For this, it is important to understand the new nature and features of the implementation of pedagogical management in the context of the global digitalisation process.Aim. The aim of the paper is to comprehend the systemic changes associated with pedagogical management in the digital educational environment, to study the new content of the structural components of pedagogical management.Methodology and research methods. The present research was carried out in reliance on the system-activity, subject-personal and environmental approaches. Theoretical and empirical research methods were used. The online survey method formed the basis of the research. The respondents were young practice teachers studying for a master degree in the direction of “Pedagogical Education”. They begin their professional activities at the stage of the formation of a digital society; they will have to implement blended (distance, digital) learning. The authors applied the methods of comparative and contrastive analysis (comparison of the nature of management in a classical (classroom) and digital environment), synthesis and systematisation of data, modelling. Additionally, the methods of statistical analysis were used.Results. The necessity of a systematic understanding of pedagogical management in the context of digitalisation was substantiated. The essence of the concept of “pedagogical management in digital educational environment” was clarified. The features and nature of pedagogical management in digital educational environment were determined, its structural components were highlighted: motivational-target, information-content, organisational-activity and control-evaluative. The vectors of strengthening the professional training of specialists in the field of education were determined.Scientific novelty. The novelty of the research lies in the systemic understanding of the category of pedagogical management in the new digital conditions; in the system-functional description of the digital educational environment management model. It manifests itself in the possibility of revising the professional training programme for future teachers in the context of the digital transformation of the educational process, as well as building innovative educational practices at different levels of education, taking into account the new model of pedagogical management in digital educational environment.Practical significance. It is advisable to use the results of the study to improve the quality of professional training of teachers in digital and blended learning, improve programmes and courses of advanced training, to increase the efficiency of autonomous educational and cognitive activities, implemented with digital tools and technologies, at different levels of education. The material of the article can be useful for specialists studying the issues of pedagogical management in vocational education.